Toughness investigation on ferrous-nonferrous weld metal joint (galvanized iron-aluminium alloy) - Muhammad Fakhrul, Hashim (2013)
Dissimilar metal welding is still a new field that need more scientific research in order to apply in industry. This thesis deals in study and finding the toughness of welded of galvanized iron and aluminium alloy. The objective of this study are to investigate of toughness of dissimilar metal welding between galvanized iron (GI) and aluminium alloy (AA1100) and also to study optimize parameters of dissimilar metal welding by using aluminium filler AA5356 using Taguchi method. Nine experiments need to be conducted, and then toughness, hardness and microstructure test were conducted. The parameters used are current (110 A, 115 A, 120 A), voltage (17V, 18 V, 19 V), speed (3 mm/s, 4 mm/s, 5 mm/s) and angle (0°, 15°, 35°). From the result, it can be seen that current is the most influential parameter followed by speed and voltage in toughness and also based on Taguchi analysis, the optimize parameter is Current (115 A), Voltage (17 V) and Speed (5 mm/s), this optimize parameter were verified through confirmation experiment. The Regression analysis shows the equation of toughness strength. The microstructure observation shows common defects happen on dissimilar metal welding.